The Effectiveness of Women and Girls Safe Spaces: A Systematic Review of Evidence to Address Violence Against Women and Girls in Humanitarian Contexts. (October 2022) - Stark, Lindsay; Robinson, Mackenzie V.; Seff, Ilana; Gillespie, Alli; Colarelli, Jonathan; Landis, Debbie
One in three women and girls will experience violence in their lifetime. In conflict and postconflict settings, the incidence of violence against women and girls (VAWG) is exacerbated, resulting in increased negative social, economic, health, and psychosocial effects. In an attempt to prevent and respond to the occurrence of VAWG in humanitarian settings, Women and Girls Safe Spaces (WGSS) have been promoted as a promising intervention. The authors conducted a systematic review to examine the current quantitative evidence available on the impact and effectiveness of WGSS programs. The authors reviewed relevant peer-reviewed and gray literature using predefined search terms for potential inclusion. Seven records met inclusion criteria. Records included evaluations of WGSS programs implemented in the Democratic Republic of the Congo, Ethiopia, Uganda, Tanzania, Kenya, Bangladesh, and Pakistan. While none of the studies reported reductions in exposure to or incidence of VAWG among program participants, three evaluations demonstrated moderate improvements in psychosocial well-being, social support, and attitudes toward rites of passage. Additionally, only three of the seven evaluations employed rigorous methodologies. This study illustrates the paucity of existing quantitative evidence around the impact of WGSS and the need for further research examining the potential benefits of this widely implemented intervention for women and girls. A stronger evidence base has the potential to inform policy and program development and to help governments, organizations, and communities better allocate limited resources in response to VAWG.